(untitled) (Global Journal of Medical Research, 2021)
Pancreatic cancer is comparatively rare but extremely lethal. In the United States, pancreatic cancer is the 4 th leading cause of cancer death, and in Europe, it is the 6 th . Though Pancreatic cancer remains incurable if detected late, research into improving the therapeutic strategy has increased significantly in recent years. However, it is ambiguous if sustained improvements have been achieved by identifying the most prominent risk factors responsible for cancer. In this article, we studied the survival times of 677 pancreatic cancer patients with fifteen risk factors. The semi-parametric Cox proportional hazard (CPH) model was used to examine the covariate effect taking into account all of the statistically significant risk factors and their significant twoway interactions. A careful and rigorous assessment of the risk factors based on the AIC of the stepwise selection technique revealed seven risk factors, and ten interaction terms are statistically significantly contributing to the survival times. The final Cox-PH model was wellvalidated and satisfied all the key assumptions. The identified risk factors and their interactions are ranked according to the prognostic effect on the survival time based on the hazard ratio. We found the most contributing risk factor is the combined effect of patients with emphysema and cancer stage regional with a hazard ratio (HR) = 8.84.